Epidemiological trends of severely immunosuppressed people living with HIV at time of starting antiretroviral treatment in China during 2005–2018. Issue 3 (March 2022) - Hou, Yuying; Liu, Jiaye; Zhao, Yan; Wu, Yasong; Ma, Ye; Zhao, Decai; Dou, Zhihui; Liu, Zhongfu; Shi, Ming; Jiao, Yanmei; Huang, Huihuang; Wu, Zunyou; et al.
Highlights: The proportion of treatment-naïve severely immunosuppressed PLWHs was levelling off since 2015 (remained 11-12%). After starting ART, the early mortality of those PLWHs showed a decreasing trend during 2005-2018, but still remained at high level. The higher mortality was associated with initiation of ART in the early period, older age, lower CD4 counts, coinfection with HCV or TB. There were various trends of distribution in spatial, temporal and population for these PLWHs. Abstract: Objectives: High HIV-related mortality is mainly associated with severe immunosuppression (CD4 count < 50 cells/μL) in people living with HIV (PLWH). This study intended to explore the trends in epidemic and early mortality among PLWH with severe immunosuppression for further targeted intervention. Methods: We extracted the data of treatment-naïve PLWH with severe immunosuppression from China's National Free Antiretroviral Treatment (ART) Program database. Early mortality (within 6 or 12 months after initiating ART) and spatial, temporal, and population distribution were analyzed during 2005–2018. Results: Of 748, 066 treatment-naïve PLWH, 105, 785 (14.1%) were severely immunosuppressed PLWH aged more than 15-year-old. The proportion of severely immunosuppressed PLWH peaked at 31.4% and then decreased with time, leveling off at approximately 11–12% from 2015 onward. Early mortality rates of these PLWH declined significantly (from 17.0% to 8.1% after 6 months of initiating ART; 20.4% to 10.6% after 12 months; both p values < 0.01) from 2005–2007 to 2016–2018. In the South-central and Southwest, the number of these PLWH was larger than that in the other regions during 2005–2018, and it increased to 4780 (37.1%) and 3370 (26.2%) in 2018. The proportion of PLWH aged 30–44 years among all treatment-naïve severely immunosuppressed PLWH in each region was higher than that of other age groups during 2005–2018. After the proportion decreased during 2005–2007, the proportion of PLWH aged 45–59 years in Southwest and South-central were increased steadily from 11% (69/626) and 16.7% (358/2140) in 2007 to 33.8% (1138/3370) and 34.0% (1626/4780) in 2018, respectively; the proportion of PLWH aged ≥60 years showed an increasing trend during 2005–2018; while changes in the proportion of those age groups were less pronounced in North and Northeast. The proportion of PLWH infected by heterosexual contact was high at 83% (2798/3370) in Southwest, and 75.1% (3588/4780) in South-central in 2018; conversely, proportion of PLWH infected by homosexual contacts was largest in North (57.8% [500/865]) and Northeast (59.9% [561/936]). Conclusions: The persistent burden of treatment-naïve PLWH with severe immunosuppression remains challenging. Our results provide evidence for policy-makers to allocate resources and establish targeting strategies to identify early infection of PLWH.